Living queer history : remembrance and belonging in a southern city - Rosenthal, Gregory Samantha, 1983- (University of North Carolina Press, 2021)
"Living Queer History tells the story of an LGBTQ community in Roanoke, Virginia, a small city on the edge of Appalachia. Interweaving historical analysis, theory, and memoir, Gregory Samantha Rosenthal tells the story of their own journey--coming out and transitioning as a transgender woman--in the midst of working on a community-based history project that documented a multigenerational southern LGBTQ community. Based on over forty interviews with LGBTQ elders, Living Queer History explores how queer people today think about the past and how history lives on in the present"--